2020
DOI: 10.1016/j.vetmic.2020.108859
|View full text |Cite
|
Sign up to set email alerts
|

A chimeric influenza hemagglutinin delivered by parainfluenza virus 5 vector induces broadly protective immunity against genetically divergent influenza a H1 viruses in swine

Abstract: Highlights An HA-based vaccine candidate, created by DNA shuffling (HA-113), can be immunogenic when the recombinant antigen is expressed by PIV5 (PIV5-113). Immunity induced by the PIV5-113 vaccine can protect mice against infection with 4 of 5 parental HAs used to create the vaccine. Immunity induced by PIV5-113 can protect pigs against infection with an influenza virus isolate that is known to be infectious in pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Our results expand previously published increases in the levels of humoral and cellular responses against various pathogens by PIV5-based candidate vaccines in mice, hamsters, guinea pigs, ferrets, dogs, monkeys and most recently in humans ( 25 , 27 , 52 59 ). For the influenza virus, these immune responses protected mice and pigs against a virus challenge ( 60 ). Thus, through parental PIV5 safety, broad cell tropism, cross-species applicability, needle-free delivery, evasion of pre-existing anti-PIV5 immunity, and induction of CD8 + T cells, and mucosal and systemic antibodies, the PIV5 vector is a strong candidate for a versatile vaccine platform.…”
Section: Discussionmentioning
confidence: 99%
“…Our results expand previously published increases in the levels of humoral and cellular responses against various pathogens by PIV5-based candidate vaccines in mice, hamsters, guinea pigs, ferrets, dogs, monkeys and most recently in humans ( 25 , 27 , 52 59 ). For the influenza virus, these immune responses protected mice and pigs against a virus challenge ( 60 ). Thus, through parental PIV5 safety, broad cell tropism, cross-species applicability, needle-free delivery, evasion of pre-existing anti-PIV5 immunity, and induction of CD8 + T cells, and mucosal and systemic antibodies, the PIV5 vector is a strong candidate for a versatile vaccine platform.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses containing the PB1 gene from either PR8 or CA04 viruses were created as 1:7 reassortants using the well-established, eight-plasmid reverse genetic system, as described previously ( 59 61 ). Plasmids for PR8 and CA04 viruses were kindly provided by Richard J. Webby, St. Jude Children’s Research Hospital, Memphis, TN.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the candidate vaccine could be used to induce broad immunity against genetically diversified influenza viruses circulating in both pigs and humans. 91 However, B cells are mostly restricted to recognizing surface antigens (e.g., viral spike proteins). Once inside cells, intracellular pathogens are not readily accessible to antibodies.…”
Section: The Immunogenicity Of Piv5 As a Vaccine Vectormentioning
confidence: 99%
“…One study selected four parental influenza A H1N1 strains (A/New Jersey/8/76, A/Iowa/1/06, A/Ohio/1/07, and A/Tennessee/1‐560/09) to represent distinct phylogenetic clades and evaluated the immunogenicity of PIV5‐vectored vaccines expressing chimeric HA antigen (PIV5‐113) in a murine challenge model, before further assessment of protective immunity in a nursery pig model. The resulting data showed that the levels of vaccine‐induced HA‐reactive antibodies against ME08 (non‐parental H1N1 influenza A virus strain used to assess cross‐reactivity) were significantly higher in animals immunized via a prime‐boost regimen of PIV5‐vectored vaccine 91 …”
Section: Piv5‐based Vaccine Candidates Against Infectious Diseasementioning
confidence: 99%
See 1 more Smart Citation